Self-Monitoring Strengthening System Based on Carbon Fiber Laminate. (2nd June 2016) - Krzywon, Rafal; Gorski, Marcin; Dawczynski, Szymon; Szojda, Leszek; Castro Gomes, Joao; Salvado, Rita
Abstract : Externally bonded composites reinforced with high-strength fibers are increasingly popular in construction, especially in structures' strengthening, where the best possible mechanical properties are required. At the same time the ability to autodetect threats is one of the most desirable features of contemporary structures. The authors of the paper have developed an intelligent fabric, wherein the carbon fibers play the role of not only tensile reinforcement but also strain sensor. The idea is based on the construction of the strain gauge, where the thread of carbon fibers arranged in zig-zag pattern works as electrical conductor and is insulated by parallel thread of glass or acrylic fibers. Preliminary laboratory tests were designed to create effective measurement techniques and assess the effectiveness of the strengthening of selected building structures, as reinforced concrete and timber beams. Presented in the paper, selected results of these studies are very promising, although there were some noted problems to be considered in next steps. The main problem here is the control of the cross section of the fibers tow, affecting the total resistance of the fabric. One of the main deficiencies of the proposed solution is also sensitivity to moisture.